Cross-flow microfiltration of a high strength industrial wastewater: Modelling of membrane fouling mechanisms - Amosa, Mutiu Kolade; Jami, Mohammed Saedi; Al-Khatib, Ma'an Fahmi Rashid (2016)
Freshwater has become the blue gold of the 21st century due to its continuous depletion resulting from expanding population, shifting climates, urbanization and industrialization, and waterways pollution. Water reclamation is an orthodox alternative drought-proof source of water, and utility of membrane technology seems indispensable to every effective reclamation and reuse program due to its excellent features. However, fouling is a limiting factor of membrane separations, and in order to control particulate fouling at the design stage and plant operation monitoring, tools utilized in evaluating the particulate content of feed-water in predicting membrane fouling are vital. Subsequent to an adsorption process, a downstream cross-flow microfiltration (MF) membrane process was carried out on the final discharge effluent of palm oil mill industry at constant transmembrane pressures (TMPs) of 40 kPa, 80 kPa, and 120 kPa for 60 min filtration time using MF membranes of 0.1 and 0.2 μm pore sizes. Darcy’s law and Hermia’s blockage models were fitted to the experimental data and it was observed that cake filtration could be best used to explain the fouling mechanisms of effluent on the membranes based on the R2 values generated for the two MF membranes at all TMPs, however, not without the complete, standard and intermediate blocking mechanisms contributing at the onset of the filtration process. This demonstrates that the fouling was as a result of gradual reversible cake deposition which could easily be removed by less onerous cleaning methods. This data could serve as requisite for future upscaling of membrane processes for characteristically similar effluents with the aim of achieving sustainable fluxes.